Bit-lit. (Economist, 2020)
The article presents information on the software called Generative Pre-Trained Transformer 3 (GPT-3) that was developed by OpenAi, an artificial-intelligence (AI) laboratory based in San Francisco, California with the held of Elon Musk, founder of SpaceX. It mentions that facial-recognition systems, do better with white faces than black ones, since white faces are more common in their training sets. It presents views of AI expert Michael Nielsen, on the GPT-3.